Pengetahuan dan Keinginan Pasien pada Sarana Pelayanan Kesehatan Gigi di Kecamatan Padang Utara Melakukan Vaksinasi COVID-19 - Safira Aziza; Susi Susi; Harfindo Nismal (Andalas Dental Journal, 2023)
Background: Vaccination is an action to raise immunity actively by injecting an antigen substance to trigger the formation of antibodies to be immune from the disease or only experience mild symptoms. According to data from the Padang City Health Office, the North Padang sub-district is included in 5 sub-districts with low vaccination coverage. Objective: This study aims to determine the relationship between knowledge and the intention of dental clinic patients to carry out COVID-19 vaccination in the sub-district area of Padang Utara. Methods: This research is an analytical study using a Cross-Sectional design study approach with chii-square test. The sample in this study was 107 respondents using purposive sampling techniqueobtained from research questionnaires filled out by respondents. Data analysis using univariate and bivariate analysis processed by using SPSS.Results: 58.9% of respondents have good knowledge about vaccinating, and 66.4% are willing to vaccinate. 23.8% of respondents who had good knowledge but had a low intention to carry out COVID-19 vaccination, and as many 76.2% of respondents who had good knowledge with a high intention to carry out COVID-19 vaccination and obtained significant results with a p-value = 0.005 (<0.05)..Conclusion: There is a correlation between dental clinic patients’ knowledge of dental health service facilities in the sub-district area of Padang Utara with the intent to conduct COVID-19.